2023
DOI: 10.1136/bmjhci-2022-100704
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of electronic health record systems to enhance the quality of healthcare in low-income countries: a systematic review

Misganaw Tadesse Woldemariam,
Worku Jimma

Abstract: BackgroundElectronic health record (EHR) systems are mentioned in several studies as tools for improving healthcare quality in developed and developing nations. However, there is a research gap in presenting the status of EHR adoption in low-income countries (LICs). Therefore, this study systematically reviews articles that discuss the adoption of EHR systems status, opportunities and challenges for improving healthcare quality in LICs.MethodsWe used Preferred Reporting Items for Systematic Reviews and Meta-An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Our findings revealed that clinicians reported high satisfaction with digital hospitals and positively viewed data accessibility in quantitative measures; however, our qualitative evidence synthesis revealed themes of frustration with slow digital workflows and inconsistent data discoverability. Evidence of EMR adoption in low-income countries also highlights clinician perception of the EMR as a key facilitator and interoperability and clinician burnout as barriers, similar to our findings on the impact of EMR on workload and burnout symptoms [107].…”
Section: Principal Findings and Comparison With Prior Worksupporting
confidence: 86%
“…Our findings revealed that clinicians reported high satisfaction with digital hospitals and positively viewed data accessibility in quantitative measures; however, our qualitative evidence synthesis revealed themes of frustration with slow digital workflows and inconsistent data discoverability. Evidence of EMR adoption in low-income countries also highlights clinician perception of the EMR as a key facilitator and interoperability and clinician burnout as barriers, similar to our findings on the impact of EMR on workload and burnout symptoms [107].…”
Section: Principal Findings and Comparison With Prior Worksupporting
confidence: 86%
“…For example, to address interoperability challenges, these countries should prioritize solutions that promote seamless integration of healthcare activities and departments. This involves providing comprehensive training programs and ongoing support to facilitate the transition from paper-based to electronic systems [5]. Another critical aspect that needs to be addressed during the successful implementation of EMRs is technological limitations.…”
Section: Interventions To Effective Emr Implementation In the Develop...mentioning
confidence: 99%
“…Therefore, only electronic records or software compatible with existing technology infrastructure should be selected. Later on, with the passing years, increased communication between healthcare providers and IT project managers will help healthcare authorities overcome organizational barriers, and software with even the latest and more advanced features will be successfully implemented [5]. Developing countries must also prioritize confidentiality, integrity, access control, and audit trail mechanisms to safeguard electronic records effectively, for which they can seek guidance and support from experienced nations to design foolproof data preservation protocols.…”
Section: Interventions To Effective Emr Implementation In the Develop...mentioning
confidence: 99%
“…Studies have shown that EHR systems can improve patient care, increase patient participation, improve care coordination, and enhance patient safety (Eduhealthsystem, 2022;Woldemariam & Jimma, 2023). However, the implementation of EHR systems in low-middle income countries (LMICS) has been challenging due to poor infrastructure, lack of management commitment, standards, interoperability, support, experience, and poor EHR systems (Woldemariam & Jimma, 2023;Bisrat et al, 2021;Silwamba, 2019).…”
Section: Statement Of the Problemmentioning
confidence: 99%